Der gymnasiale Lektürekanon in Slowenien in der Zeit der Habsburger Monarchie - Samide, Irena (Primerjalna književnost, 2014)
The paper analyses on the basis of empirical historical-descriptive research the gradual canonization of austrian playwright Franz Grillparzer in high schools in Slovenia in Austria-Hungary, points to the differences between the theatre and school reception, assigns Grillparzer in the broader context of high school literary canon and reveals reasons for his decanonization.
Keywords: Grillparzer, Franz, 1791-1872; avstrijska književnost; avstrijska dramatika; recepcija v Sloveniji; literarni kanon; slovensko gledališče; gimnazijski pouk; domovinska vzgoja